Darmstadt Rotor No. 2, II: Design of Leaning Rotor Blades - Jörg Bergner (International Journal of Rotating Machinery, 2003)
For Darmstadt University of Technology's axial singlestage transonic compressor rig, a new three-dimensional aft-swept rotor was designed and manufactured at MTU Aero Engines in Munich, Germany. The application of carbon fiber–reinforced plastic made it possible to overcome structural constraints and therefore to further increase the amount of lean and sweep of the blade. The aim of the design was to improve the mechanical stability at operation that is close to stall.